EDUCATIONAL TERRITORY, TEACHING AND LEARNING STYLES IN NON-FORMAL SPACES: AN EXPERIENCE REPORT AT THE BUTANTAN INSTITUTE - de Jesus, Cecília Souza; dos Santos, Marcio Eugen Klingenschmid Lopes; Alves, Taila dos Santos; Cavaletto, Marcia Valeria Massa; de Souza, Renata Ferraz; Pedroso, Ana Paula Turesso Pinto; de Oliveira, Cristiano Augusto; Benites, Junio Cesar Lima (Editora Impacto Científico, 2025)
This paper analyzes the teaching and learning experience of Vocational and Technological Education students during a technical visit to the Butantan Institute in São Paulo. The activity aimed to articulate theory and practice, enabling direct contact with scientific research, institutional history, and the observation of biological phenomena in a non-formal educational setting. Thirty students from the second year of the Interior Design technical course at the Vasco Antonio Venchiarutti Technical School (Jundiaí/SP) participated. The methodology adopted was descriptive, based on teacher observation and reflective analysis of the reports produced by the students after the visit. The results revealed high engagement, scientific curiosity, and a broader understanding of topics related to the immune system, vertebrates, microbiology, and conservation practices. Interaction with the Vaccine, Historical, Biological, and Microbiological Museums enhanced learning, allowing students to establish connections between previously studied content and observed phenomena. Furthermore, the development of cognitive, ethical, social, and investigative skills was highlighted, especially through practical activities such as the cultivation of microorganisms. It is concluded that the technical visit to the Butantan Institute promoted meaningful, contextualized learning aligned with the different learning styles of the students, highlighting the importance of non-formal spaces as educational territories that strengthen teaching and bring science, school, and society closer together.DOI: https://doi.org/10.56238/edimpacto2025.084-022